2014
DOI: 10.5455/2320-6012.ijrms20140257
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of epithelial cell abnormalities in Pap smears and its clinicopathological and demographic association: a descriptive study from Visakhapatnam city, Andhra Pradesh, India

Abstract: Cervical cancer is the second most common cancer among females worldwide and the most common cancer among females in developing countries including India. 1,2 The importance of cervical cancer further lies in the fact, that the natural history has a long latent phase which enables detection and treatment of the premalignant lesions. The Pap screening test provides a simple, easy and effective means of identifying these lesions 2,3 and the ABSTRACT Background: Cervical cancer is one of the leading cancers among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…From various studies, it is seen that the prevalence of CIN in present study is almost equal with the study conducted by Sinha P et al 3 and Gupta N et al 4 Most cases of severe dysplasia were found in the age group of 41-50 and 51-60 years. It correlates with the findings by Al-Jashamy K. 7 and A. Bhagya Lakshmi et al 8 The incidence of squamous cell carcinoma was also highest in the same age group. This finding supports the theory of evolution of invasive carcinoma from the preceding lesion, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…From various studies, it is seen that the prevalence of CIN in present study is almost equal with the study conducted by Sinha P et al 3 and Gupta N et al 4 Most cases of severe dysplasia were found in the age group of 41-50 and 51-60 years. It correlates with the findings by Al-Jashamy K. 7 and A. Bhagya Lakshmi et al 8 The incidence of squamous cell carcinoma was also highest in the same age group. This finding supports the theory of evolution of invasive carcinoma from the preceding lesion, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…cervix in a slum area of the city showed that epithelial cell abnormalities were identified by Pap smears in 30 women (16.1%). 5 King George hospital in the city is among the oldest hospitals in the country, catering to people from coastal Andhra Pradesh and adjoining areas of Orissa and Madhya Pradesh. The obstetrics and gynecology services were among the first to be commissioned in the fledgling institute.…”
mentioning
confidence: 99%